Variance swap replication: Discrete or continuous? - Fabien Le Floc'h (Journal of Risk and Financial Management, 2018)
The popular replication formula to price variance swaps assumes continuity of traded option strikes. In practice, however, there is only a discrete set of option strikes traded on the market. We present here different discrete replication strategies and explain why the continuous replication price is more relevant.
Keywords: 330; variance swap; volatility; derivatives; quantitative finance